Rheological Behaviour and Thermal Conductivity of Polyvinyl Ether Lubricant Modified with SiO2-TiO2 Nanoparticles for Refrigeration System. (June 2022) - Ismail, M.F.; Azmi, W.H.; Mamat, R.; Rahim, R. Ab
Abstract: Before any nanolubricant is being applied in a refrigeration system, its thermo-physical properties shall be investigated. In this paper, hybrid nanolubricant is prepared by dispersing SiO2 -TiO2 nanoparticles at 50:50 composition ratio into the polyvinyl ether (PVE) compressor lubricant using a two-step method. The investigation was done for volume concentrations from 0.01 to 0.10% under temperature range of 303 to 353 K. The Newtonian behaviour of the nanolubricant was obtained, and relative thermo-physical enhancement was determined by comparing its performance to the pure lubricant. It was observed that the maximum increment viscosity does not exceed 3% from the base fluid, while thermal conductivity for 0.1% concentration increases up to 1.6%. Overall observation also reveals that both rheological and thermal properties increase by increasing concentrations, but the same properties decrease with temperature. An interesting finding is the nanolubricant had viscosity decrement than the pure lubricant specifically at 303 K. New regression models were suggested for thermo-physical properties with high accuracy R-squared values of 0.9989 and 0.9920 for viscosity and thermal conductivity, respectively. As a conclusion, SiO2 -TiO2 /PVE nanolubricant is recommended in refrigeration systems with a volume concentration of less than 0.10%.